Uruguay (International Monetary Fund, 2022)
Uruguay entered the pandemic with solid institutions and social cohesion but growing macroeconomic imbalances-especially slow economic growth and weak public finances-as the end of the last commodity price boom in 2014 uncovered structural weaknesses. A new government came to power in March 2020 with a mandate to boost growth and restore fiscal sustainability. Legislation setting the foundations for many of the reforms has been passed and implementation is advancing–including on a new fiscal rule, and state-owned enterprise (SOE) and pension reforms
10.5089/9798400200236.002
Keywords: Graue Literatur; inflation expectation; Uruguayan peso; countercyclical monetary policy tool; Policy recommendation; government finance statistics yearbook; monetary policy transmission; liability positions vis-à-vis nonresident; Global; Caribbean; COVID-19; Fiscal stance; Inflation; Public sector; International Agreements and Observance; International Organizations; Monetary Policy; Statistics; Public Finance; Debt; Debt Management; Sovereign Debt; Health Behavior; Fiscal Policy; Price Level; Deflation; Data Collection and Data Estimation Methodology; Computer Programs: Other; Monetary economics; International institutions; Public finance & taxation; Infectious & contagious diseases; Macroeconomics; Econometrics & economic statistics; Civil service & public sector; International organization; Public debt; Money and Monetary Policy; Health; International Economics; Diseases: Contagious; Economic sectors; Monetary policy; International agencies; Debts; Public; Communicable diseases; Fiscal policy; Prices; Finance; Public